Screen time and physical activity behaviours are associated with health-related quality of life in Australian adolescents. - Lacy, K; Allender, S; Kremer, P; de Silva-Sanigorski, A; Millar, L; Moodie, M; Mathews, L; Malakellis, M; Swinburn, B (2012)
PURPOSE: To explore the cross-sectional relationships between health-related quality of life (HRQoL) and physical activity (PA) behaviours and screen-based media (SBM) use among a sample of Australian adolescents. METHODS: Data came from baseline measures collected for the It's Your Move! community-based obesity prevention intervention. Questionnaire data on sociodemographics, PA, SBM and HRQoL were collected from 3,040 students (56% boys) aged 11-18 years in grade levels 7-11 in 12 secondary schools. Anthropometric data were measured. RESULTS: The highest level of PA at recess, lunchtime and after school was associated with higher HRQoL scores (boys, by 5.3, 8.1, 6.3 points; girls, by 4.2, 6.1, 8.2 points) compared with not being active during these periods. Exceeding 2 h of SBM use each day was associated with significantly lower HRQoL scores (boys, by 3.2 points; girls, by 4.0 points). Adolescents who were physically active and low SBM users on school days had higher HRQoL scores (boys, by 6.6 points; girls, by 7.8 points) compared with those who were not physically active every school day and high SBM users on school days. CONCLUSIONS: Several of the relationships between low PA and high SBM use and HRQoL were comparable to those previously observed between chronic disease conditions and HRQoL, indicating that these behaviours deserve substantial attention.